Pemahaman Masyarakat Terhadap Hukum Islam di Era Digital - Diandra Joy Hutapea; Gelora Rehliasta Sembiring; Yunita Tri Carnova Manurung; Syuratty Manalu (Universitas Sains dan Teknologi Komputer, 2024)
. In the digital era, technology has brought significant changes in people’s lives, including in religious practices. However, the complexity of digital technology can also present challenges for people to maintain a spiritual connection with their religion. One of the biggest challenges in developing a spiritual connection in cyberspace is the increasing use of social media. It is also important that Islamic legal education in the digital era continues to evolve with the times to advance the civilization of the next generation. Religious leaders must be able to adapt to technological developments and manage content and attitudes to respond to the digital era in order to maintain interfaith relations. Islam has many teachings to maintain and build interfaith communication. Therefore, the public understanding of Islamic law in the digital era requires a wise approach to ensure that religious values are maintained in the context of evolving technology.